Spreading suppression and the guidance of search by movement: evidence from negative color carry-over effects. - Dent, K; Humphreys, G; Braithwaite, J (2011)
A growing number of studies have shown that significant impairments to search and selection can occur if the target item carries a feature of the irrelevant distractors currently being ignored Braithwaite, Humphreys, and Hodsoll (Journal of Experimental Psychology: Human Perception and Performance, 29, 758-778, 2003). However, these effects have been documented only when search has been extended over time (i.e., in preview search), and not in standard search displays with simultaneously presented items. Here, we present the first evidence that similar costs to selection can occur in simultaneous displays under appropriate circumstances. In the present experiment, participants searched a display for a moving target letter among static and moving distractors. Search efficiency was significantly enhanced for a moving target when half of the letters moved (and half remained static), allowing the static items to be excluded from search. However, if the moving target then shared its color with the irrelevant static items, significant costs emerged, relative to baselines. These results are consistent with the involvement of a general feature-based suppression mechanism in selection, operating over space as well as time.